Avaliação das propriedades químicas e geomecânicas de agregados oriundos de jazidas de rochas de diferentes litologias do estado do RS. - Back, Ana Helena (2018)
The evaluation of the chemical and geomechanical properties of rocky materials requires the testing of technological characterization of their granular materials through specific methodologies, which will allow qualifying and quantifying the parameters of interest according to the desired application, guaranteeing the safety and the life of the design of the road structure. The present research aims to contribute to the national database through the study of different rocky materials coming from different lithologies found in the territory of Rio Grande do Sul, associating their geological origins with their physical and geomechanical characteristics, as well as the survey of parameters and correlations between them. The initial stage consisted of a detailed survey of geological and geotechnical information about the characteristics detected along the rocky massifs, through field investigations followed by laboratory tests of chemical, physical and mechanical characterization, able to determine the properties and technological characteristics of the aggregates. The characterization was performed in laboratories belonging to the Universidade Federal de Santa Maria and in the Laboratory of Geotechnics of the Instituto Alberto Luiz Coimbra de Pós-Graduação e Pesquisa de Engenharia, including tests to evaluate mineralogical and textural composition, mechanical resistance, degree of absorption, shape of particles, alterability under the use of chemical agents, etc. The laboratory parameters were obtained by comparing them with information obtained on the characteristics of the rock massif, such as the degree of alteration and discontinuity structures, in order to detect a pattern of behavior between the different materials and the influence of the characteristics of the massif in the final performance of the crushed aggregate. The field stage was fundamental for understanding and knowledge of the behavioral characteristics of the different rock formations, becoming essential for understanding the influence of rock massif properties on the laboratory performance of the aggregate. In addition, it was verified that the physical indexes of the rocks are influenced directly by the mineralogical composition and structural characteristics. Regarding the mechanical degradation tests, all the rocks exhibited linear adjustments significantly satisfactory for both analyzes. It was verified that the mechanical performance of the plutonic acidic igneous is strongly influenced by the mineralogical and textural characteristics in comparison to the physical indexes, which, due to the greater number of planes of weakness, tends to suffer greater mechanical degradations.